Preventable Blindness due to Ankyloblepharonin Stevens- Johnson SyndromeA Case Report - Goswami, Manash Kumar; Asaduzzaman, Md (BIRDEM Medical Journal, 2017)
Stevens-Johnson syndrome (SJS) is common, having long term ocular complications ranging from dry eye to loss of vision due to ankyloblepharon or corneal opacities. Proper medical management and separating the bulbar conjunctiva from palpebral regularly by a glass rod during the acute phaseof the diseases can prevent the development of ankyloblepharonand symblepharon. Here we present a case of ankyloblepharon after SJS which was repaired after 6 months in the department of ophthalmology, BIRDEM General Hospital. Birdem Med J 2016; 6(2): 136-138